Réponses

  • Utilisateur Brainly
2014-03-22T09:35:44+01:00
C) 2x+ 4+3x sur 5 = 2 -x-6 sur 10
2x+4+3/5x=2-x-3/5
on multiplie par 5
10x+20+3x=10-5x-3
7x+20=-5x+7
12x=-13
x=-13/12

d) 7x-14 sur 21 - 39 sur 52= 5x sur 30
7x-14/21-39/52=5/30x
7x-2/3-3/4=x/6
on multiplie par 12
84x-8-9=2x
82x=17
x=17/82

e) 3x-7 sur 8 - 5x-1 sur 16 = 3-2x sur quatre -1

3x-7/8-5x-1/16=3-2x/4-1
on multiplie par 16
48x-14-80x-1=48-8x-16
-32x-15=-8x+32
-24x=47
x=-47/24
Meilleure réponse !
2014-03-22T10:14:45+01:00
C) 2x+ 4+3x sur 5 = 2 -x-6 sur 10
   5x+4/5=-x-4/10
  2(5x+4)/2*5=-x-4/10
  10x+8/10=-x-4/10 1/10 s'élimine
   10x+8=-x-4
   10x+x=-4-8
    11x=-12
     x=12/11
d) 7x-14 sur 21 - 39 sur 52= 5x sur 30
    7x-14/21 -39/52=5x/30
    7x-2/3-39/52=x/6
    7x-x/6 = 2/3+39/52
    7*6x/6-x/6=2*52/52*3+3*39/52x3
    42x/6-x/6=104/156+117/156
   41x/6=221/156
      x=221/156 * 6/41
      x=221*6/156*41
     x=221*6/26*6*41
     x=221/26*41
     x= 13*17/2*13*41
     x=17/41*2
     x=17/82    
e) 3x-7 sur 8 - 5x-1 sur 16 = 3-2x sur quatre -1
     (3x-7)/8-(5x-1)/16 = (3-2x)/4
-1
    2(3x-7)/2*8-(5x-1)/16 = (3-2x)/3
   ( 6x-14)/16-(5x-1)/16=(3-2x)/3
    (6x-14-5x+1)/16=(3-2x)/3
    (x-13)/16=(3-2x)/3
    3(x-13)=16(3-2x)
    3x-39=48-32x
    32x+3x=48+39
    35x = 87
       c=87/35